Organizational, design and technology issues in the process of protection of underground historic monuments = Problemy organizacyjne, projektowe i technologiczne w procesie zabezpieczania zabytkowych podziemi - Bartos, Maciej; Chmura, Janusz; Wieja, Tomasz (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
Underground historic monuments constitute the immanent part of the cultural and natural heritage. Protecting and opening underground historic objects, as the investment aim, is a process of renewed actions taken in objects that are degraded or out of order, contributing to improvement of quality of life of residents, restoring new functions, reconstruction of social bonds.
Keywords: podziemne obiekty zabytkowe; obiekty zabytkowe; dziedzictwo kulturowe; zrównoważony rozwój; strategia ochrony; underground historic monuments; protection policy; renovation; cultural heritage; sustainable development